Can Reduced Provision of Manufactured Feed Improve Fish Production Efficiency in Ponds?. (10th December 2012) - Filbrun, Jesse E.; Culver, David A.
Abstract: Fish culturists strive to efficiently transfer energy from manufactured feed to the fish crop while minimizing adverse impacts on the environment and water quality. In this study, we sought to improve production of age‐1 Channel Catfish Ictalurus punctatus by testing the effects of full (3% of body weight [BW]/d) and reduced (1% BW/d) feeding rates on fish diets, growth, and survival; lower‐trophic‐level dynamics; and water quality in earthen ponds. Fish survival was similar between feeding treatments, although length, weight, and yield at harvest were lower for 1% BW/d ponds. Using stable N and C isotopes, we found that the percent contribution of natural prey to Channel Catfish tissue growth was higher for 1% BW/d ponds (median = 74%) than for 3% BW/d ponds (55%). In both feeding treatments, small fish (those with initial BWs < 15 g) had variable diets that included both natural prey and feed, whereas all of the larger fish (>15 g) depended mainly on feed for growth. Reducing the feeding rate decreased neither plankton abundances nor nutrient concentrations in ponds, but it did increase dissolved oxygen levels. We recommend that managers carefully consider the ecological role of feed in ponds and the usage of feed by fish to implement context‐dependent sustainable feeding methods. For example, implementing the reduced feeding rate of 1% BW/d may increase the efficiency of producing Channel Catfish at sufficient sizes for stocking into natural waters without reducing survival in the hatchery.